Effect of Hispanic Status in Mechanical Thrombectomy Outcomes After Ischemic Stroke: Insights From STAR. Issue 11 (14th September 2021) - Burks, Joshua D.; Chen, Stephanie H.; Luther, Evan M.; Almallouhi, Eyad; Al Kasab, Sami; Jabbour, Pascal M.; Wolfe, Stacey Q.; Fargen, Kyle M.; Arthur, Adam S.; Goyal, Nitin; Fragata, Isabel; Maier, Ilko; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Epidemiological studies have shown racial and ethnic minorities to have higher stroke risk and worse outcomes than non-Hispanic Whites. In this cohort study, we analyzed the STAR (Stroke Thrombectomy and Aneurysm Registry) database, a multi-institutional database of patients who underwent mechanical thrombectomy for acute large vessel occlusion stroke to determine the relationship between mechanical thrombectomy outcomes and race. Methods: Patients who underwent mechanical thrombectomy between January 2017 and May 2020 were analyzed. Data included baseline characteristics, vascular risk factors, complications, and long-term outcomes. Functional outcomes were assessed with respect to Hispanic status delineated as non-Hispanic White (NHW), non-Hispanic Black (NHB), or Hispanic patients. Multivariate analysis was performed to identify variables associated with unfavorable outcome or modified Rankin Scale ≥3 at 90 days. Results: Records of 2115 patients from the registry were analyzed. Median age of Hispanic patients undergoing mechanical thrombectomy was 60 years (72–84), compared with 63 years (54–74) for NHB, and 71 years (60–80) for NHW patients ( P <0.001). Hispanic patients had a higher incidence of diabetes (41%; P <0.001) and hypertension (82%; P <0.001) compared with NHW and NHB patients. Median procedure time was shorter in Hispanics (36 minutes) compared to NHB (39 minutes) and NHW (44 minutes) patients ( P <0.001). In multivariate analysis, Hispanic patients were less likely to have favorable outcome (odds ratio, 0.502 [95% CI, 0.263–0.959]), controlling for other significant predictors (age, admission National Institutes Health Stroke Scale, onset to groin time, number of attempts, procedure time). Conclusions: Hispanic patients are less likely to have favorable outcome at 90 days following mechanical thrombectomy compared to NHW or NHB patients. Further prospective studies are required to validate our findings.